2017
DOI: 10.1038/aps.2017.30
|View full text |Cite
|
Sign up to set email alerts
|

Chrysin ameliorates podocyte injury and slit diaphragm protein loss via inhibition of the PERK-eIF2α-ATF-CHOP pathway in diabetic mice

Abstract: Glomerular epithelial podocytes are highly specialized cells that play a crucial role in maintaining normal function of the glomerular filtration barrier via their foot processes. Chrysin (5,7-dihydroxyflavone) is a natural flavonoid found in propolis and mushrooms that has anti-inflammatory, antioxidant and anticancer properties. This study aimed to evaluate the renoprotective effects of chrysin on podocyte apoptotic loss and slit diaphragm protein deficiency in high glucose-exposed podocytes and in db/db mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 41 publications
(68 reference statements)
4
44
0
Order By: Relevance
“…Similarly, chrysin, a natural flavonoid, attenuates podocytes apoptosis in diabetic mice via the inhibition of the ER stress-mediated PERK-eIF2α pathway. 48 …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, chrysin, a natural flavonoid, attenuates podocytes apoptosis in diabetic mice via the inhibition of the ER stress-mediated PERK-eIF2α pathway. 48 …”
Section: Discussionmentioning
confidence: 99%
“…In turn, these conditions cause irreversible podocyte injury and dysfunction, which decrease the number of podocyte [ 6 ]. Podocyte damage and loss seriously damage the integrity of the glomerular filtration barrier, leading to proteinuria and podocyte injury and promoting glomerular sclerosis, which accelerate the progression of diabetic nephropathy [ 7 ]. In our study, we found significant differences in the morphological, structural, and functional aspects of podocytes in the kidney tissues of rats with DN compared with those in the NC group.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, eucalyptol maintained robust filtration slits and normal foot processes of podocytes. Similarly, the flavone chrysin ameliorates slit diaphragm protein loss via the inhibition of endoplasmic reticulum stress in diabetic mice . However, there is a lack of effective therapeutic drugs to maintain the podocyte integrity.…”
Section: Discussionmentioning
confidence: 99%